Semiclassic models of the dissipative regime of instability and superradiation of a quantum radiator system - Kuklin, V.M.; Lazurik, V.T.; Poklonskiy, E.V.; Куклін, В.М.; Лазурик, В.Т.; Поклонский, Є.В. (My University, 2021)
The paper discusses the similarity between dissipative generation and superradiance regimes for systems of excited quantum emitters placed in an open cavity. In the case of the existence of a resonator field due to reflections from the ends of the system, a dissipative generation regime is usually realized. In this case, the decrement of oscillations in the waveguide in the absence of radiators turns out to be greater than the increment of the arising instability of the system of radiators placed in the resonator. When describing this mode, the influence of the emitters on each other and the sum of their own fields is neglected. The resonator field forces the oscillators to emit or absorb quanta synchronously with it, depending on the local value of the population inversion. Lasing takes on a weakly oscillatory character due to an asynchronous change in the population inversion of the system of emitting dipoles (nutations), which have a ground and excited energy levels. To describe the process, the equations of the semiclassical theory based on the use of the density matrix are quite sufficient. In the case when there is no resonator or waveguide field, taking into account the eigenfields of the oscillators becomes essential. To simulate the superradiance process, large emitting particles are used, to describe which one should use the equations for the density matrix. It is shown that the interaction of quantum emitters in this case is due to electromagnetic fields under conditions when the overlap of their wave functions is insignificant. Equations are obtained that allow considering the process of interaction of emitters. When the emitters interact, an integral field is formed in the resonator, an increase in the intensity of which leads to synchronization of the emitters. It is shown that the characteristic times of the development of the process, as well as the attainable amplitudes of the excited fields for dissipative regimes of generation and regimes of superradiance of emitters filling an open resonator, are comparable.
Напівклачисні моделі дисипативного режиму нестійкості та надвипромінювання системи квантових випромінювачів
У роботі обговорюється подібність дисипативних режимів генерації та режимів надвипромінювання для систем збуджених квантових випромінювачів, поміщених у відкритий резонатор. У разі існування резонаторного поля за рахунок відбиття від торців системи звичайно реалізується дисипативний режим генерації. При цьому декремент коливань у хвилеводі при відсутності випромінювачів виявляється більше інкремента виникаючої нестійкості системи випромінювачів, поміщеної в резонатор. При описі цього режиму вплив випромінювачів один на одного і сума їх власних полів нехтується. Поле резонатора змушує осцилятори випромінювати або поглинати кванти синхронно з ним, в залежності від локального значення інверсії заселеності. Генерація набуває слабо осциляторний характер через несинхронну зміну інверсії заселеності системи випромінюючих диполів (нутації), що мають основний і збуджений рівні енергії. Для опису процесу цілком достатньо рівнянь напівкласичної теорії, заснованої на використанні матриці щільності. У разі, коли резонаторне або хвилевідне поле відсутнє, врахування власних полів осциляторів стає істотним. Для моделювання процесу надвипромінювання застосовуються великі частки-випромінювачі, для опису яких слід скористатися рівняннями для матриці щільності. Показано, що взаємодія квантових випромінювачів в цьому випадку обумовлена електромагнітними полями в умовах, коли перекриття їх хвильових функцій несуттєво. Отримані рівняння, що дозволяють розглянути процес взаємодії випромінювачів. При взаємодії випромінювачів в резонаторі формується інтегральне поле, зростання інтенсивності якого призводить до синхронізації випромінювачів. Показано що характерні часи розвитку процесу, а також досяжні амплітуди збуджених полів для дисипативних режимів генерації та режимів надвипромінювання випромінювачів, що заповнюють відкритий резонатор, виявляються порівнюваними.
Keywords: дисипативні режими генерації; надвипромінювання; відкритий резонатор; dissipative regimes of generation; superradiance; open resonator